2012
DOI: 10.1002/dc.22872
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound‐guided fine‐needle aspiration diagnosis of large cell neuroendocrine carcinoma of the gallbladder and common bile duct: Report of a case

Abstract: Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) allows a reliable and accurate diagnosis of neoplasms of the gallbladder and bile ducts. We report the cytopathologic findings of a case of large cell neuroendocrine carcinoma (LCNEC) of the gallbladder and extrahepatic bile ducts in a 67-year-old woman who presented with progressive abdominal pain and jaundice. EUS-FNA of the mass involving the common bile duct and of a porta hepatis lymph node showed abundant cellularity with tumor cells arranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…Apart from the pathological immunohistochemical examinations, contrast-enhanced ultrasonography has differential clinical significance (38). Case reports using contrast-enhanced ultrasonography have revealed that biliary sludge is not enhanced (39) .In these case reports, the gallbladder polyp was enhanced with grape-like fine pedicles and the three-layer structure of gallbladder wall was clear (40) .For adenomyosis of the gallbladder, unenhanced vesiculoid echocardiography was observed and the inner and serous membranes of the gallbladder were intact (41). Gallbladder adenoma resulted in delayed enhancement that was identifiable by 'fast in and slow out' through the complete three-layer structure of the gallbladder wall (38).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Apart from the pathological immunohistochemical examinations, contrast-enhanced ultrasonography has differential clinical significance (38). Case reports using contrast-enhanced ultrasonography have revealed that biliary sludge is not enhanced (39) .In these case reports, the gallbladder polyp was enhanced with grape-like fine pedicles and the three-layer structure of gallbladder wall was clear (40) .For adenomyosis of the gallbladder, unenhanced vesiculoid echocardiography was observed and the inner and serous membranes of the gallbladder were intact (41). Gallbladder adenoma resulted in delayed enhancement that was identifiable by 'fast in and slow out' through the complete three-layer structure of the gallbladder wall (38).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…In grade I (low) and grade II (intermediate), NET are considered well differentiated tumors, as for grade 3 (high), they are called poorly differentiated NEC. [6][7][8] But recently, the new European Neuroendocrine/WHO nomenclature and classification for neuroendocrine tumors has included in addition to the grading system, the mitotic count and the Ki-67 index.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative diagnosis was possible in few cases only. 6,7 The prognosis is based on the tumor grading on pathology. They are considered benign when dealing with well to moderately differentiated cells (Grades 1 and 2) and called NET.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous report also described the advantages of cytologic examinations using endoscopic, ultrasound-guided, fine-needle aspiration samples for the early diagnosis of LCNEC in the biliary tract. 15 The histologic features of LCNEC are as follows: (1) positivity for neuroendocrine markers, among which chromogranin A and synaptophysin are the most commonly identified; (2) a mitotic count exceeding 20/10 high-power fields or a Ki67 index over 20%; and (3) a specific NET pattern of an organoid structure, rosette formation, and palisading and trabecular arrangement, as well as prominent nuclei that are more than 3-fold the diameter of a lymphocyte. 3,[5][6][7][8][9][10][11] Immunohistochemical examinations of chromogranin A, synaptophysin, CD56, and Ki67 were performed using enzyme-antibody and streptavidin-peroxidase techniques described in prior reports.…”
Section: Discussionmentioning
confidence: 99%